Prototype development of Face Recognition Door Lock Access Authorization Control and Management System - Masandig, Hannes; Baharudin, Muhammad Nazrul Alif; Yazid, Muhammad Sahadan; Mohamad, Amir Imtiaz (Multidisciplinary Applied Research and Innovation, 2022)
This system is a design and development prototype of facial recognition door lock system. Facial recognition is a part of Artificial Intelligent (AI) feature that can matching the user face from the database. A database is used to store digital images of users’ faces to increase system security from compromising its confidentiality, integrity, and availability. The system is equipped with a non -physical key which makes it very efficient to prevent burglary cases. Non -physical keys can also make it easy for users to enter the door. This report will discuss the development of a facial recognition access authorization system on door locks. The methodology that has been used is waterfall model and the development software is Thonny Python IDE. The project was put to the test on residential area users, and the results showed that 95 percent of the respondents agree that the system has the ability to prevent theft and burglary. Although the system uses Artificial Intelligent (AI) as a key feature, it still has some minor drawbacks where it takes a little more time to handle the face recognition process. However, people can trust this project because it can improve the security of the door access control system by using simple techniques like Raspberry pi.